Novel process for the synthesis of class I antiarrhythmic agent (+/-)-cibenzoline and its analogs - Gholap, Atul R.; Paul, Vincent; Srinivasan, Kumar V. (Synthetic Communications, 2008)
Synthesis of (+/-)-cibenzoline and its analogs has been achieved by a simple sequence of reactions. The diaryl cyanoolefin intermediate 3 could be prepared by Knoevenagel condensation of benzophenone with ethylcyanoacetate to form the tetra-substituted olefin intermediate 2 followed by Krapcho deethoxycarbonylation or from beta-hydroxynitrile intermediate 2' followed by the elimination of hydroxyl group respectively. The 2,2-diphenylcyclopropanecarbonitrile 4 was synthesized from intermediate 3 by cyclopropanation, which was converted to (+/-)-2-(2,2-diphenylcyclopropyl)-2-imidazoline 5 by reaction with ethylenediamine in the presence of a catalytic amount of sulfur. Moreover, the obtained 2-imidazolines were smoothly oxidized to the corresponding imidazoles 6 in good to moderate yields.
Keywords: Benzophenone; cibenzoline; cyclopropanation; diaryl cyanoolefin

Efficient, rapid, and regioselective bromination of anilines and phenols with 1-butyl-3-methylpyridinium tribromide as a new reagent/solvent under mild conditions - Borikar, Sanjay P.; Daniel, Thomas; Paul, Vincent (Tetrahedron Letters, 2009)
1-Butyl-3-methylpyridinium tribromide, [BMPy]Br(3) proves to be a highly efficient, regioselective reagent/solvent for nuclear bromination of various anilines and phenols. The synthesis and characterization of the room temperature ionic liquid [BMPy]Br(3) (2) is described. The bromination was carried out in the absence of organic solvents and in most cases the only extraction solvent needed was water. The spent 1-butyl-3-methylpyridinium bromide (1) was easily recycled. (C) 2008 Elsevier Ltd. All rights reserved.
Keywords: Bromination; Ionic liquid; Regioselective; [BMPy]Br(3)

Mild, efficient, and regioselective monobromination of arylamines and phenols using [BBIm]Br-3 as a new reagent - Borikar, Sanjay P.; Daniel, Thomas; Paul, Vincent (Synthetic Communications, 2010)
We report here an efficient method for the synthesis and characterization of the room-temperature ionic liquid 1,3-di-n-butylimidazolium tribromide ([BBIm]Br-3) (2) and its application as an efficient reagent and solvent for regioselective bromination of arylamines and phenols under mild conditions. The bromination was carried out in the absence of organic solvents, and in most cases, the only extraction solvent needed was water. The spent 1,3-di-n-butylimidazolium bromide (1) was easily recycled.
Keywords: Ionic liquid; monobromination; Regioselective; Solvent-free; [BBIm]Br3

N-nitrosation of secondary amines using p-TSA-NaNO2 as a novel nitrosating agent under mild conditions - Borikar, Sanjay P.; Paul, Vincent (Synthetic Communications, 2010)
A combination of p-toluenesulfonic acid (p-TSA) and sodium nitrite was used as a novel effective nitrosating agent for the N-nitrosation of secondary amines to their corresponding nitroso derivatives under mild and heterogeneous conditions in moderate to excellent yields.
Keywords: N-nitrosation; nitroso amines; p-toluenesulfonic acid; secondary amines

First total synthesis of 5-hydroxy-3-methyl-4-propylsulfanyl-5H-furan-2-one: a cancer chemopreventive agent - Borikar, Sanjay P.; Paul, Vincent; Puranik, Vedavati G.; Sathe, Vilas T.; Lagunas-Rivera, Selene; Ordonez, Mario (Synthesis-Stuttgart, 2011)
The first total synthesis of 5-hydroxy-3-methyl-4-propylsulfanyl-5H-furan-2-one, a newly discovered natural product with anticancer property is described by two different routes. A sequence involving an incorporation of a methyl group via a Gilman reagent and a chemoselective reduction of a cyclic anhydride functionality are the key steps. The methods proposed start from easily available starting materials and allow ready preparation of the final compound in good overall yield.
Keywords: Allium cepa; chemopreventive; Gilman reagent; selective; synthesis

Tuning spectral properties of phenothiazine based donor-pi-acceptor dyes for efficient dye-sensitized solar cells - Marszalek, Magdalena; Nagane, Satyawan; Ichake, Amol; Humphry-Baker, Robin; Paul, Vincent; Zakeeruddin, Shaik M.; Graetzel, Michael (Journal of Materials Chemistry, 2012)
Two novel metal-free organic donor-pi-acceptor dyes were synthesized using electron-rich 10-butyl-(2-methylthio)-10H-phenothiazine as a donor and cyanoacrylic acid as an acceptor. The spectral response of the dye was tuned by introducing a vinylene thiophene pi-bridge. Obtained optical and electrochemical properties of the dyes seemed to be promising in terms of employing them as light harvesters in dye-sensitized solar cells (DSCs). The efficiencies of the devices under standard AM 1.5G (100 mW cm(-2)) conditions reached 7.3% with volatile electrolyte. The differences in the photovoltaic parameters of these DSCs were explained by comparing the results of electrochemical impedance spectroscopy (EIS) measurements and transient photovoltage and photocurrent decay experiments.

Structural variations of D-pi-A dyes influence on the photovoltaic performance of dye-sensitized solar cells - Marszalek, Magdalena; Nagane, Satyawan; Ichake, Amol; Humphry-Baker, Robin; Paul, Vincent; Zakeeruddin, Shaik M.; Gratzel, Michael (RSC Advances, 2013)
Two new organic D-pi-A dyes containing identical pi-conjugated spacer and anchoring/acceptor moieties but different donor groups were designed and synthesized. These dyes containing didodecylcyclopentadithiophene (CPDT) as a spacer, cyanoacrylic acid as an acceptor and N-butyl-carbazole or N-butyl-phenothiazine moieties as electron donor groups are labelled as V4 and V11 dyes, respectively. The variation in the donor group of these two dyes, that influences the photophysical, electrochemical and photovoltaic parameters, was investigated. The highest photovoltaic conversion efficiency of 7.5% was obtained with V4 dye at AM 1.5 G full sunlight intensity (100 mWcm(-2)). Comparison of phenothiazine donor dyes with two different pi-conjugated spacers, CPDT (V11) and vinyl thiophene (V7) containing devices shows that the V-oc of V7 dye is lower than that of V11 due to the downward shift of the conduction band edge. Transient photovoltage and electrochemical impedance spectroscopy measurements were performed to explain the differences in the PV parameters by varying the donors and/or spacer groups.

Accessing polysubstituted 2-cyclopentenones via base-mediated annulation of β-keto esters and phenacyl bromides - Kumar, Mohit; Paul, Vincent; Gamidi, Rama Krishna; Senthilkumar, Beeran (Organic & Biomolecular Chemistry, 2025)
A transition metal-free method is demonstrated for the synthesis of polysubstituted 2-cyclopentenone compounds, which involves the direct annulation of phenacyl bromide with beta-keto esters in a single step. This process proceeds through a base-mediated SN2 nucleophilic substitution, followed by an intramolecular aldol condensation, resulting in the formation of three C-C bonds and one ring in a cascade manner. The experimental results achieved a record high yield of highly substituted diverse 2-cyclopentenone analogues, which exhibit very good structural resemblance to biologically significant natural compounds.